Tuanku Lintau Dalam Paderi di Tanah Datar (1803-1832) - Tuti, Hera Widyas; Zubir, Zusneli; Meldawati, Meldawati (Pendidikan Sejarah, 2013)
ABSTRACTÂ Tuanku Lintau is one of the leading personalities of the Paderi war from Lintau whose real name is Saidi Muning . Author discussed of Tuanku Lintau inside Paderi in Tanah Datar , while the extent of the problem formulation and the background, what is the background Tuanku Lintau inside Padri in Tanah Datar (1803-1832) , how Tuanku Lintau the Padri movement in Tanah Datar and where of the base area Tuanku Lintau the Padri movement in Tanah Datar . Research objectives achieved in this study were 1) to describe the beginning of lord Lintau in Padri in Tanah Datar , 2) Describe the movements performed by the lord Lintau in Padri in Tanah Datar and 3 ) Describe the base areas in the Padri movement Tuanku Lintau in Tanah Datar . This study uses historical methods is: a) heuristic, b ) source criticism, c ) analysis, d ) and d) histografi, e) systematics of writing while, patterned penilitian combined library and the instrument research source field is taken from a book, article, this research field observations and interviews conducted with the use of descriptive methods. The research results found that Muslim community at the time was entirely Tuanku Lintau but have not run completely Islamic teachings. People still believe in superstition, kurafat and bidâah, connect chickens , fighter, drinking wine and immoral form etc. Tuanku Lintau convey his message in a peaceful manner and there by force .Tuanku Lintau once ruled Tanah Datar and in part Sumpur area and skillful Fifty holy city of Islam , although not occupied Pagaruyung and the economy has been pioneering the coffers of the economy by growing rice and fishing column , but there is a political weakness Dutch have managed to pit neighbor communities ( in this case the pengulu and religion ) . The conclusion is a pioneer Tuanku Lintau war Padri in Tanah Datar as fighters and defensive characteristics , such as movements of religious movements , political , economy, the movement against the indigenous and colonial Dutch , regional base-base and Tuanku Lintau remainder.Â Key Words: Tuanku Lintau, Paderi, Tanah Datar.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â